2022
DOI: 10.1177/27541223221143986
|View full text |Cite
|
Sign up to set email alerts
|

E-commerce: A platform for local economic development? Evidence from Taobao Villages in Zhejiang Province, China

Abstract: In contrast to the one village one product (OVOP) and joint action (JA) models, e-commerce disintermediation is the focus of the Taobao village (TV) model pioneered in China. Drawing on original questionnaire survey data of village heads’ perceptions of the adoption of the TV model in 300 Taobao villages in Zhejiang province, we investigate: (1) the significance of the TV phenomenon; (2) the perceived benefits and disbenefits of the adoption of the Taobao business model on villages; (3) and the institutionalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Their research indicated that the lack of effective policy support and regulation could lead to unfair competition and risks. On the other hand, Phelps et al (2022) proposed the potential of e-commerce in creating employment opportunities in rural areas. Their research indicated that the development of e-commerce platforms could stimulate local economic growth and promote the emergence of small and startup businesses, thus creating more job opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Their research indicated that the lack of effective policy support and regulation could lead to unfair competition and risks. On the other hand, Phelps et al (2022) proposed the potential of e-commerce in creating employment opportunities in rural areas. Their research indicated that the development of e-commerce platforms could stimulate local economic growth and promote the emergence of small and startup businesses, thus creating more job opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Digital technology plays a crucial role in improving the quality of agricultural information services, facilitating the integration of digital economy and characteristic agriculture, and fostering new rural business forms. Furthermore, rural e-commerce has the potential to revolutionize the rural circulation service system, mitigate information asymmetry in the agricultural market, and boost the agricultural economic cycle [24]. Second, digital village construction can deepen rural services for the benefit of the people.…”
Section: Introductionmentioning
confidence: 99%